The method of developing the power supply system for electric rental go-kart - Mateja, Krzysztof (Technical Sciences, 2023)
This article presents the results of work related to the power supply system for 10kW electric, rental go-kart. The research took into account a few types of battery cells. For the case study, the best option was chosen taking into account the restrictions included in the multicriteria analysis for further application. Chosen BLDC motor and battery type were tested on test stands and simulated in MATLAB/Simulink. Simulation model allowed to compare the characteristics from test stands and simulation and next tune the model. Minimum capacity of the batteries had to allow for at least 20 minutes of drive. Chosen elements: electric motor, motor controller, battery cells, BMS allowed to build the first prototype. Tests in real conditions showed the difference between simulation and research system. We could notice what to improve to tune the simulation model and the kart power supply system.